2011
DOI: 10.1016/j.devcel.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic Neuropeptide Oxytocin Is Required for Formation of the Neurovascular Interface of the Pituitary

Abstract: SUMMARY The hypothalamo-neurohypophyseal system (HNS) is the neurovascular structure through which the hypothalamic neuropeptides oxytocin and arginine-vasopressin exit the brain into the bloodstream, where they go on to affect peripheral physiology. Here, we investigate the molecular cues that regulate the neurovascular contact between hypothalamic axons and neurohypophyseal capillaries of the zebrafish. We developed a transgenic system in which both hypothalamic axons and neurohypophyseal vasculature can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 60 publications
6
64
0
Order By: Relevance
“…To examine the possibility of an AgRP2 neurovascular connection in the hypophysis, we crossed agrp2 :mCherry with Tg( kdrl :EGFP) S843 fish (which expresses EGFP in vascular endothelial cells47). Examination of transgene expression in this cross showed that AgRP2 terminals are juxtaposed with vessels that have been designated as the hypophysial artery42 (Fig. 3f,g).…”
Section: Resultsmentioning
confidence: 98%
“…To examine the possibility of an AgRP2 neurovascular connection in the hypophysis, we crossed agrp2 :mCherry with Tg( kdrl :EGFP) S843 fish (which expresses EGFP in vascular endothelial cells47). Examination of transgene expression in this cross showed that AgRP2 terminals are juxtaposed with vessels that have been designated as the hypophysial artery42 (Fig. 3f,g).…”
Section: Resultsmentioning
confidence: 98%
“…These neurons reside in the ancestral preoptic nucleus (PON; Diepen, 1962; Figure 1), which became recently a subject of genetic studies, using transgenic fish models (Gutnick et al, 2011; Herget et al, 2013). Magnocellular neurons of adult Anamnia are quite randomly distributed within the PON, existing intermingled with other types of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Once at the NH, however, H-NH axons play a crucial role in shaping NH vasculature. Studies in zebrafish show that the neurotransmitter Oxytocin-like (referred to as Oxytocin), released by neurohypophyseal nerve endings, can promote vessel growth (Gutnick et al, 2011). Nevertheless, it remains unclear whether other factors operate alongside Oxytocin, potentially contributing to the H-NH vascularisation profile.…”
Section: Introductionmentioning
confidence: 99%